Protective effects of formalin- and heat-killed Aeromonas hydrophila in nile tilapia (Oreochromis niloticus) infection - Pimentel, Stephanie S. (Transactions of the National Academy of Science and Technology, 2011)
Aeromonas hydrophila is an opportunistic bacterial pathogen of a number of aquatic animals that causes hemorrhagic septicemias, erythrodermatitis, fin and tail rot in fish. The pathogen affects Oreochromis niloticus (Nile tilapia), an economically important cultured fish in the Philippines. In this study, the protective effects of formalin- or autoclave niloticus then challenged with live A. hydrophila. Data on mortality rates, serum lysozyme levels and histopathology of immune related organs, head, kidney and spleen, generated responses in the challenged fish. Though fish were not entirely protected from live form, autoclaved-killed bacteria showed stronger immune responses compared to formalin-killed bacteria.